Il monitoraggio dell’esposizione al rischio sismico dei centri storici italiani - Benetti, Donatella; Cara, Pierluigi (GEOmedia, 2012)
Il Sistema WEB CSRS - Centri Storici e Rischio Sismico è uno strumento condiviso di indagine per il monitoraggio dell'esposizione al rischio sismico dei centri storici italiani, attraverso una rete nazionale di scambio di informazioni tra diversi livelli di governo territoriale. Abstract The monitoring of exposure to seismic risk of the Italian historical centers The Italian territory is densely populated and anthropized; on it there are heritage buildings built mostly in not recent age. The historic centers are the most important example of cultural heritage in the anthropic landscape. For the Civil Protection Department is pressing the necessity of a survey aimed at assessing the "cultural interest” of the historic centers and the risk of losses to which they are exposed, for the application of policies prevention and planning for risk reduction. In accordance with Ministry of Cultural Heritage and Activities, was implemented the Web system CSRS, shared with all levels of land government, for the monitoring of seismic risk with the collection, in interoperability via standard network services, of information (including maps) about exposure and vulnerability of historical centers.